PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PPKN DI KELAS IV MI MUHAMMADIYAH BUNTU BARANA - Sulistianingsih; Suherman; Saleha (STKIP Subang, 2026)
Sulistianingsih, 2026. The Implementation of the Talking Stick Method to Improve Students’ Learning Motivation in Civics Education for Fourth Grade Students at MI Muhammadiyah Buntu Barana. Thesis. Supervisor I: Suherman, S.Pd., M.Pd and Supervisor II: Saleha, S.Pd., M.Pd. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Enrekang.This study aims to determine the process of implementing the Talking Stick method to improve students’ learning motivation in Civics Education for fourth grade students at MI Muhammadiyah Buntu Barana. The research used Classroom Action Research (CAR) consisting of planning, action implementation, observation, and reflection stages. The subjects of this study were all fourth grade students. Data collection techniques were carried out through observation to measure students’ learning motivation during the learning process. The results of the study showed that the implementation of the Talking Stick method was able to improve students’ learning motivation. This could be seen from the improvement of students’ learning mastery in each learning cycle. The conclusion of this study is that the Talking Stick method is effective in improving students’ learning motivation in Civics Education on the topic “Cooperation in My Environment” at elementary school level.